Influência da gestão e do controle familiares e do fundador sobre o endividamento das empresas abertas brasileiras: evidências empíricas - Segura, Liliane Cristina (2012)
This research investigated the influence of family and founder on the debt of Brazilian listed companies. Despite the vast national and international literature on capital structure, there are still some doubts about the importance of family in business management. In Brazil, due to the large number of family businesses and concentrated control, is even more evident the need to investigate the issue. Many other studies have treated the family business, others control the concentration and others, the company's founder. The contribution of this work was to separate the companies that have concentrated control in the hands of one family, who have only the family influence, family control, those whose management is familiar and the other whose management is only the founder and also the founder of management company family.Furthermore, it was the separation of concentrated control, significant influence, management controlling, managing shareholder influence. In total 10 different separations were made and tested along the work. The study population consisted of companies listed on Bovespa in 2009, and the final sample consisted of 365 companies. As the main contribution of this work was used as a classification different from the other by separating control and influence,combining the family and the founder and principal actors. To this end, we observed six years (2004-2009), a total of 2190 observations. These data constitute an unbalanced panel that was treated by linear regression using ordinary least squares, then by random effects and finally by fixed effects. These techniques were applied to any distortions that diminish in relation to the control variables that were used and these panels might catch the best way to control and influence of the founder family and management in enterprises. The results show that companies with family control and the ones that have some influence of the founder is present in the sample studied, presented less debt than other companies, going according to national and international studies that claim that family businesses tend to be more conservative in their investments, looking to use more equity than others. However, companies that have concentrated control in the hands of one owner or company presented more debt than the others, confirming the studies that indicate the concentration of capital in Brazil and its consequent tendency to the expropriation of wealth by the majority shareholders .